AI ethics with Chinese characteristics? Concerns and preferred solutions in Chinese academia - Zhu, Junhua (SPRINGER, 2023)
Since Chinese scholars are playing an increasingly important role in shaping the national landscape of discussion on AI ethics, understanding their ethical concerns and preferred solutions is essential for global cooperation on governance of AI. This article, therefore, provides the first elaborated analysis on the discourse on AI ethics in Chinese academia, via a systematic literature review. This article has three main objectives. (1) to identify the most discussed ethical issues of AI in Chinese academia and those being left out (the question of "what"); (2) to analyze the solutions proposed and preferred by Chinese scholars (the question of "how"); and (3) to map out whose voices are dominating and whose are in the marginal (the question of "who"). Findings suggest that in terms of short-term implications, Chinese scholars' concerns over AI resemble predominantly the content of international ethical guidelines. Yet in terms of long-term implications, there are some significant differences needed to be further addressed in a cultural context. Further, among a wide range of solution proposals, Chinese scholars seem to prefer strong-binding regulations to those weak ethical guidelines. In addition, this article also found that the Chinese academic discourse was dominated by male scholars and those who are from elite universities, which arguably is not a unique phenomenon in China.